(untitled) (American Journal of Islam and Society, 2005)
Southeast Asian Islam is receiving an increased amount of attention among both scholars and students. The direction has been toward understanding Muslim diversity and change, despite the still-existing perceptions among the public of a monolithic and static Islam. Fundamentalism still gains more attention, partly due to its current influence and confusion. In this book, Giora Eliraz comparatively examines how the Middle Eastern Islamic modernist movements influenced Islamic movements in the Malay-Indonesian world throughout the twentieth century and contributed to the rise of contemporary Islamic radicalism in Indonesia. Eliraz studies the transmission of modernist and/or radical ideas from the Middle East to Indonesia, the multiple organizations and strategies within Islamic movements, as well as the impacts of local and national values on the distinct faces of Indonesian Islam. Despite the current emergence of Islamic radicalism, the majority of the people continue to reject politicized Islam. According to the author, the tradition of intellectual and organizational pluralism has become the predominant characteristic of Indonesian Islam. The book is divided into three chapters. Chapter 1 examines how the reformist ideas of Muhammad Abduh (1849-1905), his colleague Jamaluddin al-Afghani (1839-97), and Muhammad Rashid Rida (1865-1935) were transmitted to Southeast Asia (including Indonesia and the Malay Peninsula) through publications and networks, and how they were interpreted and applied within the new environment. Thus, Islamic reformist ideas, particularly from Egypt, influenced the rise of as well as the conflicts between the modernists, represented by the Muhammadiyah (established in 1912), and the traditionalists, represented by the Nahdatul Ulama (NU, established in 1926). In these two movements, Middle Eastern reformism underwent a process of localization that involved local preachers, activists, and scholars ...